Iatrogenic Pleural Effusion Due to Extravasation of Parenteral Nutrition via an Epicutaneo Cava Catheter in Neonates: A Prospective Cohort Study - Yu, Xinying; Wang, Xuejun; Fan, Ling; Cao, Na; Yang, Fan; Li, Jiujun; Jiang, Hong (Frontiers in Pediatrics, 2020)
Background: Although Epicutaneo cava catheters (ECCs) are being routinely used for intravenous access for long-term parenteral nutrition and prolonged medication administration in neonates, ECC use can be associated with rare but acute life-threatening events such as pleural effusion (PE). It is important to identify and maintain the ECC tip in a central location for preventing complications. Recently, intracavitary electrocardiogram (IC-ECG) has been developed for the real-time monitoring and verification of ECC tip position. Objective: To investigate the causes and preventive measures of ECC-related PE in neonates. Methods: This prospective cohort study was conducted between January 2013 and December 2017. We observed and analyzed the clinical characteristics and causes of ECC-related PE. From January to December 2017, all ECCs were guided by IC-ECG. The incidence of ECC-related PE and first-attempt success rates were analyzed before and after the introduction of IC-ECG. Additionally, the sensitivity and specificity of IC-ECG were evaluated. Results: ECC-related PE was identified in 14 infants. Catheters were malpositioned in three cases; in the other 11 cases, catheters were located centrally on insertion but had migrated to noncentral locations at the time of PE. After the introduction of IC-ECG, the incidence of PE was zero (P<0.05). The incidence of ECC-related PE was lower when veins of the lower extremities were selected as the insertion site (P<0.05). The first-attempt success rate was significantly higher in the group with IC-ECG-guided ECC placement than in the group without (P<0.05). The sensitivity and specificity of IC-ECG were 97.9% and 84.6%, respectively. Conclusion: ECC-related PE can be associated with either primary malposition or migration of the catheter tip. IC-ECG can help detect malposition and migration of catheter tips and improve the first-attempt success rate. Choosing a lower extremity insertion site may help decrease the rate of ECC-related PE. In neonates, IC-ECG is a reliable positioning method for ECCs with superior sensitivity and specificity.